La regulación de la tributaciòn de ganancias ilícitas en la legislación Peruana 2003-2015 - Quispe Mendoza, Roberto (2019)
In the present research work we aim to make an analysis of the problem on the regulation of the taxation of illicit proceeds in the Peruvian legislation 2003-2015 in Peru, for this we used as a methodology the revision of the standard both at the Resolution level Tax Court and Constitutional Resolution, as well as the participation of a magistrate of the Court of Justice of La Libertad and accountants specialized in Tax Matters, being the sample of 13 resolutions of the Tax Court, Resolution of the Constitution and interview of specialist in the matter as collegiate public accountants . In doctrinal matters, all the Peruvian legislation in force was resorted to, in addition to various studies related to the tax crime.